Valorization of kiwifruit production: leaves of the pruning branches of Actinidia deliciosa as a promising source of polyphenols - Henriques, Joana (2017)
The present work concerns the novel application of a phenolic compound extraction methodology to leaves of Actinidea deliciosa. Recent studies have shown that crop residues could be raw material for recovery of natural bioactive compounds. Phenolic compounds from Actinidea deliciosa leaves were extracted with hot water, purified using reverse phase chromatography and mucilage precipitation with ethanol. The composition of the purified fraction was determined by HPLC-DAD and LC-MSn. Quercitrin, rutin, proantocyanidin B and C, quinic acid, myricitrin, and triterpene acid-O-hexoside were found. These compounds were present in all the fractions. The antioxidant activity was determined as general radical scavenging capacity, lipid peroxidation prevention, and NO radical scavenging activity. Values of EC50 of 9.4 mu g/mL, IC50 of 152.5 mu g/mL, and IC50 of 81 mu g/mL were determined, respectively. The best period of the year to obtain a high fraction of phenolic compounds (120 A mu g/mg of extract) from A. deliciosa leaves was December. The phenolic fraction obtained with hot water and ethanol precipitation is a promising good source of natural bioactive compounds and an easy method of taking advantage of the leaves from A. deliciosa. To the best of our knowledge, there are no previous works on the use of the residual leaves of this fruit tree. Several phenolic compounds with high antioxidant activity were extracted and identified in this plant for the first time.